Formic acid solder paste for chip packaging as well as preparation method and application of formic acid solder paste
By using reasonably prepared solder paste formic acid in chip packaging, the problem of insufficient solder paste solder paste in the prior art is solved, and higher solder quality and packaging efficiency are achieved, cracks and pores of the solder layer are reduced, and cracks and pores are improved. The mechanical properties and corrosion resistance of welding are provided.
Patent Information
- Application Number
- CN202411422567.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
The soldering quality and packaging efficiency of existing solder pastes between the chip and the substrate are limited, and cannot meet product performance requirements.
The solder paste for chip packaging with a total weight of 100%, including 5% to 15% flux and 85% to 95% lead-free solder powder, wherein the lead-free solder powder is composed of tin silver copper alloy particles of different particle sizes. After reasonable preparation, apply it to the substrate and perform reflow soldering.
It improves welding quality and packaging efficiency, reduces cracks and pores in the solder layer, forms a highly uniform solder layer, and enhances the mechanical properties and corrosion resistance of the solder.
Smart Images

Figure BDA0005081246370000121 
Figure BDA0005081246370000122 
Figure BDA0005081246370000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solder paste, and in particular to a formic acid solder paste for chip packaging and a preparation method and application thereof. Background Art
[0002] In the semiconductor packaging process, surface mount technology (SMT) is usually used to solder electronic components (such as chips, etc.) to the pads of the substrate. In the SMT patch processing process, the selection of solder paste is crucial, which can directly affect the welding quality, packaging efficiency and performance of the final product. However, in the related art, the improvement of the welding quality and packaging efficiency between the chip and the substrate by solder paste is limited, resulting in the performance of the final product failing to meet the demand. Therefore, it is urgent to provide a chip packaging formic acid solder paste that can effectively improve the welding quality and packaging efficiency between the chip and the substrate. Summary of the invention
[0003] In view of this, the present invention provides a formic acid solder paste for chip packaging and a preparation method and application thereof. The formic acid solder paste for chip packaging can improve the welding quality between the chip and the substrate and the packaging efficiency.
[0004] In a first aspect, an embodiment of the present invention provides a formate solder paste for chip packaging, wherein the formate solder paste for chip packaging, based on 100% of the total weight, comprises:
[0005] Flux, 5% to 15%;
[0006] Lead-free solder powder, 85% to 95%,
[0007] The lead-free solder powder includes a first lead-free solder powder having a particle size d1 less than or equal to 8 μm, a second lead-free solder powder having a particle size d2 greater than 8 μm and less than or equal to 15 μm, and a third lead-free solder powder having a particle size d3 greater than 15 μm and less than or equal to 25 μm. The particle size distribution of the first lead-free solder powder in the lead-free solder powder is 10% to 20%, the particle size distribution of the second lead-free solder powder in the lead-free solder powder is 25% to 40%, and the particle size distribution of the third lead-free solder powder in the lead-free solder powder is 50% to 65%.
[0008] According to any of the aforementioned embodiments of the present invention, the lead-free solder powder comprises tin-silver-copper alloy particles, wherein the mass content a1 of silver in the first lead-free solder powder, the mass content a2 of silver in the second lead-free solder powder and the mass content a3 of silver in the third lead-free solder powder satisfy a1; a2: a3 = (7-9): (5-6): (3-4).
[0009] According to any of the aforementioned embodiments of the present invention, a1 is 3.75% to 4%;
[0010] and / or, a2 is 3% to 3.2%;
[0011] And / or, a3 is 1.9% to 2.1%.
[0012] According to any of the aforementioned embodiments of the present invention, the mass content b1 of silver and copper in the first lead-free solder powder, the mass content b2 of copper in the second lead-free solder powder and the mass content b3 of copper in the third lead-free solder powder satisfy b1; b2: b3 = (9-10): (7-8): (5-6).
[0013] According to any of the aforementioned embodiments of the present invention, b1 is 0.9% to 1%;
[0014] and / or, b2 is 0.7% to 0.8%;
[0015] And / or, b3 is 0.5% to 0.6%.
[0016] According to any of the aforementioned embodiments of the present invention, the lead-free solder powder further includes an anti-oxidation layer, and the anti-oxidation layer is coated on the surface of the tin-silver-copper alloy particles.
[0017] According to any of the aforementioned embodiments of the present invention, the anti-oxidation layer includes nickel and chromium elements.
[0018] According to any of the aforementioned embodiments of the present invention, the thickness of the anti-oxidation layer is 10 nm to 50 nm.
[0019] In a second aspect, an embodiment of the present invention provides a method for preparing a formic acid solder paste for chip packaging as described in any embodiment of the first aspect of the present invention, comprising:
[0020] A preparation step, mixing a first lead-free solder powder having a particle size d1 less than or equal to 8 μm, a second lead-free solder powder having a particle size d2 greater than 8 μm and less than or equal to 15 μm, and a third lead-free solder powder having a particle size d3 greater than 15 μm and less than or equal to 25 μm, to obtain a lead-free solder powder, wherein the particle size distribution of the first lead-free solder powder in the lead-free solder powder is 10% to 20%, the particle size distribution of the second lead-free solder powder in the lead-free solder powder is 25% to 40%, and the particle size distribution of the third lead-free solder powder in the lead-free solder powder is 50% to 65%;
[0021] In a mixing step, the flux and the lead-free solder powder are mixed to obtain formate solder paste for chip packaging, wherein, based on 100% of the total weight of the formate solder paste for chip packaging, the weight of the flux accounts for 5% to 15%, and the weight of the lead-free solder powder accounts for 85% to 95%.
[0022] In a third aspect, an embodiment of the present invention provides an application of a formic acid solder paste for chip packaging as described in any embodiment of the first aspect of the present invention in chip packaging, comprising:
[0023] The coating process is to coat the chip packaging formate solder paste on the pad of the substrate to form a solder layer.
[0024] In the welding process, the chip is mounted on the solder layer and formic acid gas is introduced for reflow welding, so as to weld the chip on the welding pad.
[0025] A formate solder paste for chip packaging and a preparation method and application thereof are provided in an embodiment of the present invention. Based on 100% of the total weight of the formate solder paste for chip packaging, the solder paste includes: a flux, 5% to 15%; and a lead-free solder powder, 85% to 95%, wherein the lead-free solder powder includes a first lead-free solder powder having a particle size d1 less than or equal to 8 μm, a second lead-free solder powder having a particle size d2 greater than 8 μm and less than or equal to 15 μm, and a third lead-free solder powder having a particle size d3 greater than 15 μm and less than or equal to 25 μm, wherein the particle size distribution of the first lead-free solder powder in the lead-free solder powder is 10% to 20%, the particle size distribution of the second lead-free solder powder in the lead-free solder powder is 25% to 40%, and the particle size distribution of the third lead-free solder powder in the lead-free solder powder is 50% to 65%. In the above technical solution, a reasonable weight ratio of flux and lead-free solder powder can help improve the welding quality, wherein the weight ratio of flux can effectively remove oxides on the surface of the welded object, so that their surface reaches the required cleanliness, and can also prevent the re-oxidation of the surface during welding, reduce its surface tension, and improve the welding quality. The weight ratio of lead-free solder powder and the related settings of the first lead-free solder powder, the second lead-free solder powder, and the second lead-free solder powder included therein can effectively reduce cracks and pores in the solder layer formed by the solder paste, thereby further helping to improve the welding quality.
[0026] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. DETAILED DESCRIPTION
[0027] As used herein, "a", "the", "at least one" and "one or more" are used interchangeably. Thus, for example, a coating composition comprising "a" additional additive can be interpreted to mean that the coating composition comprises "one or more" additional additives.
[0028] For simplicity, some numerical ranges are disclosed herein, however, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unspecified range.
[0029] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, the enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0030] An embodiment of the present invention provides a formate solder paste for chip packaging. Based on a total weight of 100% of the formate solder paste for chip packaging, the solder paste includes: a flux, 5% to 15%; and a lead-free solder powder, 85% to 95%, wherein the lead-free solder powder includes a first lead-free solder powder having a particle size d1 less than or equal to 8 μm, a second lead-free solder powder having a particle size d2 greater than 8 μm and less than or equal to 15 μm, and a third lead-free solder powder having a particle size d3 greater than 15 μm and less than or equal to 25 μm, the particle size distribution of the first lead-free solder powder in the lead-free solder powder is 10% to 20%, the particle size distribution of the second lead-free solder powder in the lead-free solder powder is 25% to 40%, and the particle size distribution of the third lead-free solder powder in the lead-free solder powder is 50% to 65%.
[0031] In the above technical solution, a reasonable combination of the weight ratio of flux and lead-free solder powder can help improve the welding quality. Among them, the weight ratio setting of the flux can effectively remove oxides on the surface of the welded objects, so that their surfaces reach the required cleanliness, and can also prevent their surfaces from re-oxidation during welding, reduce their surface tension, and improve welding quality.
[0032] The weight ratio of the lead-free solder powder is set within the above range, which can help improve the welding effect and mechanical properties. In addition, the particle size d1 of the first lead-free solder powder is less than or equal to 8μm, the particle size d2 of the second lead-free solder powder is greater than 8μm and less than or equal to 15μm, and the particle size d3 of the third lead-free solder powder is greater than 15μm and less than or equal to 25μm, and the particle size distribution of the first lead-free solder powder in the lead-free solder powder is 10% to 20%, the particle size distribution of the second lead-free solder powder in the lead-free solder powder is 25% to 40%, and the particle size distribution of the third lead-free solder powder in the lead-free solder powder is 50% to 65%. The particle size distribution of the above lead-free solder powder can improve the wetting effect of the solder paste, and the particle size and its reasonable distribution can reduce cracks and pores in the solder layer formed by the solder paste, thereby further helping to improve the welding quality.
[0033] In the above embodiment, the particle size and distribution of the lead-free solder powder can be measured by using instruments and methods well known in the art, such as using a laser particle size analyzer to measure and obtain the particle size and distribution of the lead-free solder powder.
[0034] In an embodiment of the present invention, the metal components and their contents in the lead-free solder powder can also be reasonably configured to further reduce cracks and pores in the solder layer formed by the solder paste, while also helping to form a highly uniform solder layer, thereby further improving the welding quality.
[0035] In some embodiments of the present invention, the lead-free solder powder includes tin-silver-copper alloy particles, wherein the mass content a1 of silver in the first lead-free solder powder, the mass content a2 of silver in the second lead-free solder powder, and the mass content a3 of silver in the third lead-free solder powder satisfy a1; a2: a3 = (7-9): (5-6): (3-4).
[0036] In the above embodiment, the ratio setting of a1, a2 and a3 can help to further reduce cracks and pores in the solder layer formed by the solder paste, and can also help to improve the height uniformity of the solder layer, thereby further improving the welding quality.
[0037] Furthermore, a1 is 3.75% to 4%; and / or a2 is 3% to 3.2%; and / or a3 is 1.9% to 2.1%.
[0038] In some embodiments of the present invention, the mass content b1 of silver and copper in the first lead-free solder powder, the mass content b2 of copper in the second lead-free solder powder and the mass content b3 of copper in the third lead-free solder powder satisfy b1; b2: b3 = (9-10): (7-8): (5-6).
[0039] In the above embodiment, the ratio setting of b1, b2 and b3 can help to improve the strength and corrosion resistance of the solder layer, thereby helping to improve the welding quality.
[0040] Furthermore, b1 is 0.9% to 1%; and / or b2 is 0.7% to 0.8%; and / or b3 is 0.5% to 0.6%.
[0041] In the lead-free solder powder of the above-mentioned embodiment, the mass content of tin is the remaining ratio except for the above-mentioned components, and it can also be appropriately adjusted according to the content of each component.
[0042] In addition, the structure of lead-free solder powder can be improved to further enhance its anti-oxidation and anti-cracking properties to improve welding quality.
[0043] In some embodiments of the present invention, the lead-free solder powder further comprises an anti-oxidation layer, and the anti-oxidation layer is coated on the surface of the tin-silver-copper alloy particles.
[0044] In some embodiments of the present invention, the anti-oxidation layer includes nickel and chromium. The addition of nickel and chromium can improve the corrosion resistance and crack resistance of the solder layer, thereby further improving the welding quality.
[0045] In some embodiments of the present invention, the thickness of the anti-oxidation layer is 10 nm to 50 nm. The thickness of the anti-oxidation layer is set within the above range, which can further enhance the corrosion resistance and crack resistance.
[0046] The embodiments of the present invention have no particular restrictions on the soldering flux, and any soldering flux known in the art may be used. For example, the soldering flux may include main components such as resin (e.g., rosin, acrylic resin, etc.), activator (e.g., ethylamine, citric acid, propylamine, benzoic acid, lactic acid, etc.), thixotropic agent (beeswax, carnauba wax, etc.).
[0047] In a second aspect, an embodiment of the present invention provides a method for preparing formic acid solder paste for chip packaging as in any embodiment of the first aspect of the present invention, comprising:
[0048] A preparation step, mixing a first lead-free solder powder having a particle size d1 less than or equal to 8 μm, a second lead-free solder powder having a particle size d2 greater than 8 μm and less than or equal to 15 μm, and a third lead-free solder powder having a particle size d3 greater than 15 μm and less than or equal to 25 μm, to obtain a lead-free solder powder, wherein the particle size distribution of the first lead-free solder powder in the lead-free solder powder is 10% to 20%, the particle size distribution of the second lead-free solder powder in the lead-free solder powder is 25% to 40%, and the particle size distribution of the third lead-free solder powder in the lead-free solder powder is 50% to 65%;
[0049] In a mixing step, the flux and the lead-free solder powder are mixed to obtain formate solder paste for chip packaging, wherein based on the total weight of 100% of the formate solder paste for chip packaging, the weight of the flux accounts for 5% to 15%, and the weight of the lead-free solder powder accounts for 85% to 95%.
[0050] In a third aspect, an embodiment of the present invention provides an application of a formic acid solder paste for chip packaging in any embodiment of the first aspect of the present invention in chip packaging, comprising:
[0051] A coating process is to coat the chip packaging with formic acid solder paste on the pads of the substrate to form a solder layer;
[0052] In the welding process, the chip is mounted on the solder layer and formic acid gas is introduced for reflow welding to weld the chip on the welding pad.
[0053] In the above embodiment, formic acid gas can react with metal oxides generated during welding, that is, hydroxyl groups replace oxygen atoms to form formates, and formates decompose at high temperatures to form metal elements, thereby eliminating the adverse effects of metal oxides on welding points.
[0054] The following embodiments describe the disclosure of the present invention in more detail, and these embodiments are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present invention. Unless otherwise stated, all parts, percentages and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods, and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0055] The following embodiments describe the disclosure of the present invention in more detail, and these embodiments are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present invention. Unless otherwise stated, all parts, percentages and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized according to conventional methods, and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0056] Example 1
[0057] This embodiment provides a method for preparing formate solder paste, comprising:
[0058] The first lead-free solder powder Sn95.29Ag3.8Cu0.91, the second lead-free solder powder Sn96.18Ag3.1 Cu0.72 and the third lead-free solder powder Sn97.36Ag2.1 Cu0.54 in Table 1 are mixed to obtain lead-free solder powder;
[0059] Based on the total weight of 100% formic acid solder paste, 2% rosin, 3% citric acid, 1% beeswax, 3% diethylene glycol ethyl ether and 91% lead-free solder powder are placed in a disperser, first stirred at a stirring speed of 25 rpm / min for 25 minutes, and then the disperser is evacuated, the stirring speed is maintained under a vacuum environment, and stirring is continued for 20 minutes to obtain formic acid solder paste.
[0060] Example 2
[0061] The difference between this embodiment and Embodiment 1 lies in the particle size distribution of the first lead-free solder powder, the second lead-free solder powder and the third lead-free solder powder.
[0062] Example 3
[0063] The difference between this embodiment and Embodiment 1 lies in the particle size distribution of the first lead-free solder powder, the second lead-free solder powder and the third lead-free solder powder.
[0064] Example 4
[0065] The difference between this embodiment and Embodiment 1 lies in the particle size distribution of the first lead-free solder powder, the second lead-free solder powder and the third lead-free solder powder.
[0066] Example 5
[0067] The difference between this embodiment and embodiment 1 lies in the particle size distribution of the first lead-free solder powder, the second lead-free solder powder and the third lead-free solder powder.
[0068] Example 6
[0069] The difference between this embodiment and embodiment 1 lies in: the first lead-free solder powder is Sn95.34Ag3.75Cu0.91, the second lead-free solder powder is Sn96.28Ag3.0Cu0.72 and the third lead-free solder powder is Sn97.46Ag2.0Cu0.54.
[0070] Example 7
[0071] The difference between this embodiment and embodiment 1 lies in: the first lead-free solder powder is Sn95.09Ag4.0Cu0.91, the second lead-free solder powder is Sn96.08Ag3.2Cu0.72 and the third lead-free solder powder is Sn97.56Ag1.9Cu0.54.
[0072] Example 8
[0073] The difference between this embodiment and the first embodiment is that the first lead-free solder powder is Sn95.24Ag3.8Cu0.96, the second lead-free solder powder is Sn96.15Ag3.1 Cu0.76 and the third lead-free solder powder is Sn97.34Ag2.1 Cu0.56.
[0074] Example 9
[0075] The difference between this embodiment and the first embodiment is that the first lead-free solder powder is Sn95.2Ag3.8Cu1.0, the second lead-free solder powder is Sn96.1Ag3.1 Cu0.8 and the third lead-free solder powder is Sn97.3Ag2.1 Cu0.6.
[0076] Example 10
[0077] The difference between this embodiment and embodiment 1 is that the surfaces of the first lead-free solder powder, the second lead-free solder powder and the third lead-free solder powder are coated with a 25 nm thick anti-oxidation layer containing nickel and chromium elements. The specific method is as follows:
[0078] Argon gas is introduced at a flow rate of 120sccm. After the bias voltage is 110V, the duty cycle is 45%, the vacuum degree reaches 0.003Pa and the temperature reaches 400°C, the chromium-nickel target power supply is turned on, and deposition processing is carried out under the condition that the current of each chromium-nickel target is 50A to form an anti-oxidation layer on the surface of the lead-free solder powder.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is that the first lead-free solder powder is not included.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 1 is that there is no second lead-free solder powder.
[0083] Comparative Example 3
[0084] The difference between this comparative example and Example 1 is that there is no third lead-free solder powder.
[0085] Comparative Example 4
[0086] The difference between this comparative example and Example 1 lies in the mass content of silver in the first lead-free solder powder, the second lead-free solder powder and the third lead-free solder powder.
[0087] Comparative Example 5
[0088] The mass content of copper in the first lead-free solder powder, the second lead-free solder powder and the third lead-free solder powder.
[0089] Test Section
[0090] 1) Crack resistance test
[0091] 0.3 g of formic acid solder paste prepared in Examples 1-10 and Comparative Examples 1-5 was coated on the central part of a 0.5 mm thick substrate (an area of approximately 4 mm×4 mm) to prepare a sample, and then the sample was placed in a reflow oven and heated by introducing formic acid gas. The reflow conditions were: preheating temperature of 190°C for 90 seconds, peak temperature of 260°C for 100 seconds, and finally the cooling rate from the peak temperature to 200°C was set to 2°C / s to obtain a reflowed sample.
[0092] The sample after reflow was cut and the cross section was ground. Then, the ground cross section was observed using a scanning electron microscope to measure the size of the intermetallic compound structure precipitated in the solder after reflow, and evaluated according to the following criteria. The smaller the size of the intermetallic compound structure, the better the crack resistance. The test results are shown in Table 2.
[0093] Very good: The largest structure size observed is less than 30 μm.
[0094] Good: The maximum observed structure size is 30 μm or more and 80 μm or less.
[0095] Poor: The largest tissue size observed exceeds 80 μm.
[0096] 2) Pore area test
[0097] The formic acid solder paste prepared in Examples 1-10 and Comparative Examples 1-5 was printed onto a substrate for chip packaging, and the chip was installed by a reflow soldering method, wherein a metal mask with a thickness of 200 μm was used to adjust the printed film thickness of the solder paste. After printing the solder paste, a chip with a length of 20 mm and a width of 12 mm was installed at a specified position on the above-mentioned substrate and heated in a reflow soldering furnace. The reflow soldering conditions were: preheating temperature of 190°C, peak temperature of 250°C, and heating time of 150s.
[0098] After the substrate is cooled, the surface state of the solder on the substrate is observed through X-ray photography, and the proportion of the total area of pores in the area where solder is formed (pore area ratio) is measured. For the occurrence of pores, the average value of the pore area ratio in 10 pads on the substrate is calculated and evaluated according to the following criteria. The smaller the average value of the pore area ratio, the better the welding effect. The test results are shown in Table 2.
[0099] Very good: The average value of the pore area ratio is 4% or less.
[0100] Good: The average value of the pore area ratio is more than 4% and not more than 8%.
[0101] Poor: The average value of the porosity area ratio exceeds 8%.
[0102] 3) Solder layer height test
[0103] The formic acid solder paste prepared in Examples 1-10 and Comparative Examples 1-5 was coated on the central part of a 0.5 mm thick substrate (an area of approximately 4 mm×4 mm) to prepare a sample, and then the sample was placed in a reflow oven and heated by introducing formic acid gas, wherein the reflow conditions were: preheating temperature of 190°C, 90 s, peak temperature of 260°C, 100 s, and finally the cooling rate from the peak temperature to 200°C was set to 2°C / s to obtain a reflowed sample.
[0104] The distance from the bottom to the top of the solder layer was measured using a focal depth meter and used as the height of the solder layer. The height of the solder layer was measured at any 100 locations, and the average value (average height of the solder layer) and height deviation (standard deviation) were calculated from the measurement results. The test results are shown in Table 2.
[0105] Table 1 Particle size distribution and component content of lead-free solder powder in Examples 1-10 and Comparative Examples 1-5
[0106]
[0107] Table 2 Test results of Examples 1-10 and Comparative Examples 1-5
[0108]
[0109]
[0110] According to Table 1, by comparing the test results of Examples 1-10 and Comparative Examples 1-5, it can be seen that the embodiments of the present invention can not only effectively reduce the cracks and pores in the solder layer formed by the solder paste through the related settings of the first lead-free solder powder, the second lead-free solder powder, and the third lead-free solder powder included in the lead-free solder powder, but also make the height of the solder layer formed by the solder paste more uniform, thereby further helping to improve the welding quality.
[0111] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention. In particular, as long as there is no structural conflict, the various technical features mentioned in each embodiment can be combined in any way. The present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A formic acid solder paste for chip packaging, characterized in that: The formate solder paste for chip packaging, based on 100% of the total weight, comprises: Flux, 5% to 15%; Lead-free solder powder, 85% to 95%, The lead-free solder powder includes a first lead-free solder powder having a particle size d1 less than or equal to 8 μm, a second lead-free solder powder having a particle size d2 greater than 8 μm and less than or equal to 15 μm, and a third lead-free solder powder having a particle size d3 greater than 15 μm and less than or equal to 25 μm. The particle size distribution of the first lead-free solder powder in the lead-free solder powder is 10% to 20%, the particle size distribution of the second lead-free solder powder in the lead-free solder powder is 25% to 40%, and the particle size distribution of the third lead-free solder powder in the lead-free solder powder is 50% to 65%.
2. The formic acid solder paste for chip packaging according to claim 1, characterized in that: The lead-free solder powder includes tin-silver-copper alloy particles, wherein the mass content a1 of silver in the first lead-free solder powder, the mass content a2 of silver in the second lead-free solder powder and the mass content a3 of silver in the third lead-free solder powder satisfy a1; a2: a3 = (7-9): (5-6): (3-4).
3. The formic acid solder paste for chip packaging according to claim 2, characterized in that: a1 is 3.75% to 4%; and / or, a2 is 3% to 3.2%; And / or, a3 is 1.9% to 2.1%.
4. The formic acid solder paste for chip packaging according to claim 2, characterized in that: The mass content b1 of silver and copper in the first lead-free solder powder, the mass content b2 of copper in the second lead-free solder powder, and the mass content b3 of copper in the third lead-free solder powder satisfy b1; b2: b3=(9~10): (7~8): (5~6).
5. The formic acid solder paste for chip packaging according to claim 4, characterized in that: b1 is 0.9% to 1%; and / or, b2 is 0.7% to 0.8%; And / or, b3 is 0.5% to 0.6%.
6. The formic acid solder paste for chip packaging according to claim 2, characterized in that: The lead-free solder powder further comprises an anti-oxidation layer, and the anti-oxidation layer is coated on the surface of the tin-silver-copper alloy particles.
7. The formic acid solder paste for chip packaging according to claim 6, characterized in that: The anti-oxidation layer includes nickel and chromium elements.
8. The formic acid solder paste for chip packaging according to claim 6 or 7, characterized in that: The thickness of the anti-oxidation layer is 10 nm to 50 nm.
9. A method for preparing a formic acid solder paste for chip packaging as claimed in any one of claims 1 to 8, characterized in that: include: A preparation step, mixing a first lead-free solder powder having a particle size d1 less than or equal to 8 μm, a second lead-free solder powder having a particle size d2 greater than 8 μm and less than or equal to 15 μm, and a third lead-free solder powder having a particle size d3 greater than 15 μm and less than or equal to 25 μm, to obtain a lead-free solder powder, wherein the particle size distribution of the first lead-free solder powder in the lead-free solder powder is 10% to 20%, the particle size distribution of the second lead-free solder powder in the lead-free solder powder is 25% to 40%, and the particle size distribution of the third lead-free solder powder in the lead-free solder powder is 50% to 65%; In a mixing step, the flux and the lead-free solder powder are mixed to obtain formate solder paste for chip packaging, wherein, based on 100% of the total weight of the formate solder paste for chip packaging, the weight of the flux accounts for 5% to 15%, and the weight of the lead-free solder powder accounts for 85% to 95%.
10. Use of the formic acid solder paste for chip packaging according to any one of claims 1 to 8 in chip packaging, characterized in that: include: The coating process is to coat the chip packaging formate solder paste on the pad of the substrate to form a solder layer. In the welding process, the chip is mounted on the solder layer and formic acid gas is introduced for reflow welding, so as to weld the chip on the welding pad.
Citation Information
Patent Citations
Leadless alloy tin solder plaster and manufacturing method thereof
CN101011784A
Soldering tin paste composition and soldering-tin precoating method
CN101234455A
Lead-free solder paste for ultrafine solder powder and preparation method thereof
CN102357747A
Ultrafine low-temperature solder powder, solder paste as well as preparation method and application of solder paste
CN114055007A
Formic acid lead-free solder paste and application thereof
CN118162799A